PENDIDIKAN AGAMA: MENJAWAB TANTANGAN MODERNISASI - Abdullah, Jihan (Institut Agama Islam Negeri (IAIN) Palu, 2006)
Modernization often creates a paradigm and new values. Therefore, people who envlove in it including learners are faced with two facts; whether they are resistennt when interacting with itÂ or accept it with all its consequences. Based on this, we need supreme morality toÂ prevent or at least toÂ descrease secularism- in many occations-Â is produced by modernization.Within this context, Islamic education which has for long time been taught to students at schools,Â seems less able to-in many cases- save studentsâ morality without disregarding external factors, of course. So, whatâs actually wrong with our Islamic education.Â Kata Kunci:Â Â Â Â Modernisasi, pendidikan agama, perubahan kurikulum